Studies on Gynogenesis Induction in Cassava (Manihot esculenta Crantz) Unpollinated Ovule Culture - Lentini, Zaida; González, Álfora; Tabares, Eddie; Buitrago, María E.; Wêdzony, Maria (Frontiers in Plant Science, 2020)
Cassava (Manihot esculenta Crantz) is an important crop for subsistence farming in tropical and subtropical regions. There is a need to increase the rate of genetic gain to develop varieties adapted to new environmental conditions affected by climate change, which also influences the patterns of pests and diseases. The rate of cassava genetic improvement is limited by the difficulty in obtaining true-breeding types (inbred/homozygous lines). Cassava inbreeding obtained through conventional sequential self-pollination increases exposure of useful recessive traits and breeding value of progenitors. However, it takes 10-15 years to produce homozygous lines through successive self-pollination. Doubled haploid (DH) technology is a functional alternative to progressive self-pollination, and is already widely used in major crops to accelerate inbreeding. This work aimed at developing a protocol for the culture of isolated ovules and the induction of gynogenesis in cassava. Basic groundbreaking studies on cassava embryo sac development are presented. A protocol using unpollinated ovules collected from ovaries 1 day after anthesis is described. In the unpollinated-cultured ovules, the presence of embryos formed probably from the egg cells and not surrounded by the endosperm, was documented by anatomical analyses. This achievement is an important first step in the development of a reproducible gynogenesis protocol for the generation of doubled haploids in cassava. This protocol can also be useful as a starting point to obtain DHs using alternative methods of induction such as pollination of cassava with pollen of distant species or with cassava pollen irradiated with gamma rays.